Answer:
Step-by-step explanation:
1- Identify the x and the y
x1= -2
x2=2
y1= 2
y2= -1
2-
2- solve the equation:
d=(2-(-2)) + ((-1)-2)
d= (4) + (-3)
= 16 + 9
= 25
d=5 answer
Answer:88
Step-by-step explanation:
Answer:
Step-by-step explanation:
1) Rewrite in the form, where a = y and b = 1.
2) Use Square of Difference: .
3) Factor .
1 - Ask: Which two numbers add up to 6 and multiply to -7?
-1 and 7
2 - Rewrite the expression using the above.
Outcome/Result:
4) Rewrite the expression with a common denominator.
5) Expand.
6) Collect like terms.
7) Simplify to
Answer:
Step-by-step explanation:
It wo be B= -8
Answer:
1. b
2. a
3. d
4. c
Step-by-step explanation: